NILAI KETUHANAN DAN PESAN MORAL DALAM SYAIR TARI PAJAGA - Muh Subair (Penamas, 2016)
This paper presents the research results revealing the meaning of the poem of Pajaga dance, in order to be a provision for people to fall in love again to the local culture. This is a qualitative research conducted by interviews, observation, and literature study. Pajaga dance poem was analyzed by critical discourse analysis. The study finds out that the poem contains divinity values and moral messages in the intimate poem sentences such as: Ininnawa mapatakko, Alai pakkawaru, and Toto tellesanmu. The word Ininnawa represents the aspects of morality with a message to the man to aspire and work hard. While the meaning of the word toto is representing the power of God's will. The divinity and moral values are closely intertwined in the poem of Pajaga danceas to demonstrate that a strong expression of Godliness will bear a strong moral stance, namely a positive attitude to be a good human being, a human who keep themselves from moral turpitude. Keywords: Traditional dance, Pajaga dance poem, Divinity values, moral values. Tulisan ini menyajikan hasil penelitian yang mengungkap makna syair tari pajaga, agar menjadi bekal bagi masyarakat untuk jatuh cinta kembali kepada budaya lokalnya. Penelitian ini bersifat kualitatif yang dilakukan dengan wawancara, observasi, dan studi pustaka. Syair tari pajaga dianalisis dengan teknik analisis wacana kritis. Dari syair tersebut tampak jelas adanya nilai ketuhanan dan moral dalam kalimat syair yang begitu intim seperti dalam bait: Ininnawa mapatakko, Alai pakkawaru, Toto tellesanmu: Kata ininnawa mewakili aspek moralitas dengan pesan kepada manusia untuk bercita-cita dan berkerja keras. Sedangkan kata toto adalah mewakili makna kekuasaan takdir Tuhan. Demikian jelasnya persandingan Tuhan dan moral yang terangkai dalam syair tari pajaga, sebagai sebuah kesungguhan untuk menunjukkan, bahwa ekspresi kebertuhanan yang kuat akan melahirkan sikap moral yang kuat pula, yakni sikap positif untuk menjadi manusia yang baik, manusia yang memelihara diri dari perbuatan tercela. Kata Kunci: Tari Tradisional, Syair Tari Pajaga, nilai ketuhanan, nilai moral.